Towards an ecology of care: Basic Income after the nation-state - Linares, Julio; Cabaña, Gabriela (Society Register, 2022)
The following paper is about care1. It proposes a political vision to move towards a care-centred society that will allow the flourishing of everyone while keeping the planet inhabitable and thriving. For this utopian horizon that we name an ecology of care, we propose the creation of a Basic Income system that is constituted outside of and beyond the realm of the nation-state, as a means of changing humanity’s relationship to itself and transitioning from capitalism to a commons-based society. It argues for a disembedding of work—and the time allocated to it—from money, through a reformulation of the production of money in the form of an income distributed as an equal share to all those who are part of the planetary commons. Finally, it connects this Basic Income proposal with degrowth as a radical and necessary reformulation of society that considers its ecological roots and replaces the obsession with endless economic growth with the principle of taking care of people.